Impact of evolving surface nanoscale topologies in femtosecond laser structuring of Ni-based superalloy CMSX-4. (30th November 2015) - Li, Chen; Cheng, Guang-Hua; Colombier, Jean-Philippe; Faure, Nicolas; Reynaud, Stéphanie; Zhang, Hao; Jamon, Damien; Stoian, Razvan
Abstract: We investigate the role of surface nanoscale topographies in the inhomogeneous coupling of laser radiation to Ni-based superalloy CMSX-4 surfaces and in the formation of laser-induced periodic surface structures. The initial surface arbitrary roughness is already able, upon laser exposure, to induce low-spatial-frequency and high-spatial-frequency structures, actively determining an interference of incoming and scattered fields resulting in spatial energy modulation. A topology variation with the incoming dose via the number of pulses determines a correlated evolution in the regular ripple arrangements. The scattering pattern is severely influenced by the scattering source geometries. Therefore, we equally study experimentally the role of one-dimensional nanoscale grooves in determining polarization-dependent structuring patterns at increasing irradiation dose. Finally, the role of surface nanostructures in generating the surface modulation of deposited energy is analyzed by finite-difference-time-domain simulation. Ripple formation in multi-pulses is a result of the feedback process between light and nanostructures.